Cyclonic storm of October 1983 in the Bay of Bengal-A diagnostic study - SINGH , RANJIT; THORAT, CP (MAUSAM, 1987)
A cyclonic storm formed in the Bay of Bengal in the first week of October 1983 and crossed the coast very close to Vishakhapatnam. This gave an opportunity to study the various development aspects of a post monsoon cyclonic storm by using satellite imageries, constant pressure charts, time sections of Vishakhapatnam and cross-sections through the station. It is found that: (1) The initial development of the mid-tropospheric circulation and the low-pressure area on the sea surface took place m the same area where a cloud cluster had formed in the previous day, (2) an intense warming was generated during the development process. The maximum in warming first appeared in the upper tropospheric levels of300 hPa and 250 hPa. This phase later descended to the lower tropospheric levels. The warming was confined to Vishakhapatnam or it immediate surroundings on the south-north cross-section, (3) The maxima in temperature anomalies on the time and cross sections prepared, were overlain by the maxima in the geopotential height anomalies in the upper tropospheric levels in keeping with the hydrostatic phenomenon, (4) The maximum in the geopotential height anomalies on the cross section of 00 GMT of 3 October was associated with the formation of easterly wind maximum at the same level in its south-north section, confirming it to be the level of maximum divergence and (5) The rainfall distribution of different days showed that the maximum rainfall occurred in the forward sector of the cyclonic storm along its track .